Critical Success Factors of E-Learning Systems: A Quality Perspective: Shahid Farid, Mubashra Qadir, Moiz Uddin Ahmed,Muhammad Daud Khattak (PJDOL, 2023)
E-learning is becoming mainstream and novel driving force for the learning and training. Industry and educational institutions are investing heavily in this electronic mode of training and education because of its accessibility, ease of training, up-to-the-minute learning, effectiveness of cost and flexibility. Besides its advantages, low level of uptake in this mode of learning is perceived due to lower quality of these systems.